2021
DOI: 10.1038/s41557-021-00796-x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between nascent proteins and the ribosome surface inhibit co-translational folding

Abstract: Most proteins begin to fold during biosynthesis on the ribosome. It has been suggested that interactions between the emerging polypeptide and the ribosome surface might allow the ribosome itself to modulate co-translational folding. Here we combine protein engineering and NMR spectroscopy to characterize a series of interactions between the ribosome surface and unfolded nascent chains of the immunoglobulin-like FLN5 filamin domain. The strongest interactions are found for a C-terminal segment that is essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 65 publications
(104 reference statements)
7
57
0
Order By: Relevance
“…This conceptual shift in our understanding of protein folding further implies that the ribosome itself is likely to act as a giant chaperone and the most important part of the protein folding machinery [ 124 , 125 , 126 ]. Clearly, this possibility is fully compatible with the numerous observations indicating that folding of most if not all proteins occurs co-translationally [ 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ].…”
Section: Review Of Protein Foldingsupporting
confidence: 86%
“…This conceptual shift in our understanding of protein folding further implies that the ribosome itself is likely to act as a giant chaperone and the most important part of the protein folding machinery [ 124 , 125 , 126 ]. Clearly, this possibility is fully compatible with the numerous observations indicating that folding of most if not all proteins occurs co-translationally [ 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ].…”
Section: Review Of Protein Foldingsupporting
confidence: 86%
“…In agreement with such observation, we did not see a clear peak in pulling force for the constructs that correspond to a single repeat (L = 74) but only for constructs constituted by at least 4 repeats. For the 4 and 5 repeat constructs, the ribosome could be interacting with the exposed surfaces via electrostatic interactions ( Wruck et al, 2021 ) or unspecific binding ( Cassaignau et al, 2021 ). One could argue on the contrary, that the full protein is a completely folded domain with no available surfaces to establish productive interactions with the ribosome; therefore, its stability could be negatively affected.…”
Section: Discussionmentioning
confidence: 99%
“…The authors argue that electrostatic interactions established between the walls deep in the tunnel and the small protein are the source of this increase. Alternatively, the same kind of interactions established by a protein folding outside of the ribosome are characterized as a competition between folding and binding ( Cassaignau et al, 2021 ). These authors conceptualize the ribosome as a holdase that prevents aggregation during cotranslational folding.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the recruitment of RPBs, the ribosomal surface also directly interacts with diverse nascent polypeptides. The surface of the 50S ribosome subunit is highly acidic due to the ribosomal RNA [9] and able to constrain nascent chains via electrostatic interactions [10,11]. In addition, multiple nonpolar regions are decorated on the ribosome surface at uL23/uL29, uL24, and bL17/bL32 [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that even an intrinsically disordered nascent protein crosslinks strongly to uL23 and the neighboring uL29 in a Mg 2+ -dependent manner [12]. These ribosome-nascent chain interactions have been shown to stabilize the nascent protein in an unfolded state until downstream sequences emerge to recruit cotranslational chaperones or binding partners [10,11,17,18]. This 'holdase' activity of the ribosome allows nascent proteins to avoid local kinetic traps and thus fold productively [18].…”
Section: Introductionmentioning
confidence: 99%